Studies on Storage of Wood Apple Ready-to-serve Beverage - Zambare, A V; Patkar, S U; Kharde, Y D; Birajdar, S A; Deshpande, M M; Patil, S R; Ratnaparkhi, A H (Journal of Agricultural Engineering, 2009)
Investigations were carried out to develop a process for preparation of wood apple RTS beverage and to study the effect of storage period on its composition and quality. Preliminary trials were conducted to find out the optimum levels of juice and other ingredients for preparing RTS. RTS with two treatments viz. T1 (sodium benzoate), T2 (Potassium metabisulphite) and T3 (control) was prepared and stored at ambient temperature (35–42degree C). The samples were periodically evaluated for quality at intervals of 7 days. Results of the sensory evaluation of RTS showed that wood apple RTS beverage with 19% juice, 11.2% TSS and 0.31% acidity gave the best results in terms of overall acceptability. During the storage of RTS beverage, the TSS and acidity of the samples increased while the pH of the samples decreased as the storage period increased. Beverage preserved by using potassium metabisulphite and sodium benzoate remained above minimum overall acceptability level up to storage period of 14 weeks.